2007
DOI: 10.1146/annurev.biochem.75.103004.142647
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Function of Formins in the Control of Actin Assembly

Abstract: Formins are a widely expressed family of proteins that govern cell shape, adhesion, cytokinesis, and morphogenesis by remodeling the actin and microtubule cytoskeletons. These large multidomain proteins associate with a variety of other cellular factors and directly nucleate actin polymerization through a novel mechanism. The signature formin homology 2 (FH2) domain initiates filament assembly and remains persistently associated with the fast-growing barbed end, enabling rapid insertion of actin subunits while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
794
2
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 737 publications
(815 citation statements)
references
References 133 publications
8
794
2
11
Order By: Relevance
“…The FH2 domain nucleates and processively elongates actin filaments by associating with growing barbed ends and creating a biochemical environment favoring actin monomer addition (Kovar, 2006) (Figure 3b). mDia family formins are tightly regulated (Goode and Eck, 2007) by a Rho-controlled autoregulatory mechanism mediated by the interaction between their N-terminal (Dia-inhibitory, or DID) and C-terminal (Dia-autoregulatory, or DAD) domains (Alberts, 2001;Li and Higgs, 2005). Activated GTP-bound Rho proteins bind to the GTPase-binding domains and occlude DAD binding to DID, thus alleviating its inhibitory influence over the FH2 domain (Goode and Eck, 2007).…”
Section: Structure and Function Of Mdia Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FH2 domain nucleates and processively elongates actin filaments by associating with growing barbed ends and creating a biochemical environment favoring actin monomer addition (Kovar, 2006) (Figure 3b). mDia family formins are tightly regulated (Goode and Eck, 2007) by a Rho-controlled autoregulatory mechanism mediated by the interaction between their N-terminal (Dia-inhibitory, or DID) and C-terminal (Dia-autoregulatory, or DAD) domains (Alberts, 2001;Li and Higgs, 2005). Activated GTP-bound Rho proteins bind to the GTPase-binding domains and occlude DAD binding to DID, thus alleviating its inhibitory influence over the FH2 domain (Goode and Eck, 2007).…”
Section: Structure and Function Of Mdia Proteinsmentioning
confidence: 99%
“…mDia family formins are tightly regulated (Goode and Eck, 2007) by a Rho-controlled autoregulatory mechanism mediated by the interaction between their N-terminal (Dia-inhibitory, or DID) and C-terminal (Dia-autoregulatory, or DAD) domains (Alberts, 2001;Li and Higgs, 2005). Activated GTP-bound Rho proteins bind to the GTPase-binding domains and occlude DAD binding to DID, thus alleviating its inhibitory influence over the FH2 domain (Goode and Eck, 2007). Newly generated actin filaments provide the underlying structures that drive changes in cell morphology to facilitate events as divergent as cell division, intracellular trafficking and chemotaxis (Chhabra and Higgs, 2007).…”
Section: Structure and Function Of Mdia Proteinsmentioning
confidence: 99%
“…The first mechanism is mediated by the Arp2/3 complex (Goley and Welch, 2006;Mullins and Pollard, 1999;Welch et al, 1997;Welch and Mullins, 2002) that interacts with the surface of the existing actin filaments to create sites of branching for new actin polymerization and ensure actin assembly into the dendritic network that drives the protrusion of lamellipodia. The second mechanism is mediated by formins (Goode and Eck, 2007;Pruyne et al, 2002;Zigmond, 2004;Zigmond et al, 1998) that drive actin assembly into parallel cross-linked bundles that serve as a structural basis for filopodia.…”
Section: Basic Principles Of Cell Migration Overall Structure Of the mentioning
confidence: 99%
“…The FH2 domain is responsible for the binding to actin and for alteration of the polymerization properties of filaments. The FH1 domain can modulate this effect through interactions with profilin-actin [9][10][11]. Different formins can have other specific properties as they can depolymerise, sever or bundle filamentous actin [9,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The FH1 domain can modulate this effect through interactions with profilin-actin [9][10][11]. Different formins can have other specific properties as they can depolymerise, sever or bundle filamentous actin [9,[12][13][14][15][16]. The effect of the formins on the structure of actin has been previously investigated in the case of FH2 domain of mouse Diaphanous-related protein 1 (mDia1-FH2) and it was found that the structure of the formin-bound filaments is significantly different from those polymerized in the absence of formins.…”
Section: Introductionmentioning
confidence: 99%